UV SEDs of early-type cluster galaxies: a new look at the UV upturn. Issue 1 (29th January 2018) - Ali, S S; Bremer, M N; Phillipps, S; De Propris, R
Abstract: Using GALEX, Ultraviolet Optical Telescope (UVOT), and optical photometry, we explore the prevalence and strength of the Ultraviolet (UV) upturn in the spectra of quiescent early-type galaxies in several nearby clusters. Even for galaxies with completely passive optical colours, there is a large spread in vacuum UV colour consistent with almost all having some UV upturn component. Combining GALEX and UVOT data below 3000 Å, we generate for the first time comparatively detailed UV spectral energy distributions for Coma cluster galaxies. Fitting the UV upturn component with a blackbody, 26 of these show a range of characteristic temperatures (10 000–21 000K) for the UV upturn population. Assuming a single temperature to explain GALEX -optical colours could underestimate the fraction of galaxies with UV upturns and mis-classify some as systems with residual star formation. The UV upturn phenomenon is not an exclusive feature found only in giant galaxies; we identify galaxies with similar (or even bluer) FUV − V colours to the giants with upturns over a range of fainter luminosities. The temperature and strength of the UV upturn are correlated with galaxy mass. Under the plausible hypothesis that the sources of the UV upturn are blue horizontal branch stars, the most likely mechanism for this is the presence of a substantial (between 4 per cent and 20 per cent) Helium-rich ( Y > 0.3) population of stars in these galaxies, potentially formed at z ∼ 4 and certainly at z > 2; this plausibly sets a lower limit of 0.3- 0.8 × 10^10 M⊙ to the in situ stellar mass of ∼ L * galaxies at this redshift.